Gravitational separation of the stratospheric air over Syowa, Antarctica and its connection with meteorological fields. (25th September 2018) - Ishidoya, Shigeyuki; Sugawara, Satoshi; Inai, Yoichi; Morimoto, Shinji; Honda, Hideyuki; Ikeda, Chusaku; Hashida, Gen; Machida, Toshinobu; Tomikawa, Yoshihiro; Toyoda, Sakae; Goto, Daisuke; Aoki, Shuji; et al.
Abstract : To examine gravitational separation of the stratospheric air over Antarctica in austral summer, we collected air samples from altitudes of 10 to 30 km over Syowa Station (69.0°S, 39.6°E) using balloon‐borne cryogenic samplers for the period 1998–2013, and then analyzed them for δ 15 N of N2, δ 18 O of O2, δ(Ar/N2 ) and δ 40 Ar. The normalized mass ratio "δ, " calculated using their measured values, decreases with increasing altitude, implying an upward enhancement of the gravitational separation effect. The observed stratospheric δ profiles are generally well reproduced by a two‐dimensional atmospheric model, but the model tends to underestimate the observed δ values in the middle stratosphere above 26 km. We also observe interannual variation in the δ vertical profile in the middle stratosphere. A backward trajectory analysis suggests that this variation is attributable to different horizontal mixing of the stratospheric air over Antarctica from year to year. Abstract : Gravitational separation of the lower to middle stratospheric air, observed only by us so far, is expected be a new tool to clarify changes in circulation in the middle atmosphere. In this study, we first examined the causes of the irregular fluctuations found in each gravitational separation profile, including the profiles unpublished in our previous studies, and interpreted the fluctuations in terms of the variations in the meteorological transport fields over Antarctica.